1988
DOI: 10.1159/000281393
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Obstruction Secondary to Sigmoid Diverticulitis

Abstract: A case of ureteral obstruction secondary to diverticulitis is described. The patient had a 2-month history of lower left quadrant pain before an operation. As an intravenous pyelogram showed persistent hydronephrosis, an operation was performed. At the operation, a fibrotic mass which encased the left ureter and sigmoid colon was found. Ureterolysis and segmental sigmoidectomy were carried out. The pathological specimen showed two diverticula and subserosal cicatrization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…A study by Siminovitch et al in 1980 on 400 patients admitted with diverticulitis revealed that 5% of the patients had hydroureteronephrosis based on urograms [7]. On a review of the literature, there are scant reports documenting hydronephrosis as a complication of sigmoid diverticulitis [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Siminovitch et al in 1980 on 400 patients admitted with diverticulitis revealed that 5% of the patients had hydroureteronephrosis based on urograms [7]. On a review of the literature, there are scant reports documenting hydronephrosis as a complication of sigmoid diverticulitis [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…This also raises the question of whether hydronephrosis or ureteral involvement is a sign of impending perforation and whether patients with such presentations should undergo surgical resection. Literature is scarce regarding the conservative management of these patients as the majority of previously reported cases of diverticulitis had surgical resection [7][8][9][10][11][12]. Further retrospective studies are required to study the incidence and impact of hydronephrosis on the outcomes of patients with diverticulitis.…”
Section: Discussionmentioning
confidence: 99%